Voltametric Analysis of Ergosterol Isolated from Wild-Growing and Cultivated Edible Mushrooms from Serbia and Korea - Svetlana Đogo Mračević; Jelena Mutić; Vesna Stanković; Slavica Ražić (Molecules)
Thanks to several components with health-promoting properties, mushrooms are recognized as a practical functional food and a valuable source of nutrients for the food industry. Ergosterol, the major sterol in edible mushrooms and a precursor of vitamin D2 with proven pharmacological activity and nutritional value, has become a very important topic in chemical and medical research. The main objectives of this study were to determine the ergosterol content in different species of Serbian wild mushrooms and in commercial mushrooms from Korean and Serbian grocery stores using square-wave voltammetry, to compare the concentrations in different parts of white button mushrooms, and to determine a possible relationship between Zn, Cu and Fe and ergosterol contents. The ergosterol contents varied between 0.01 and 7.04 mg/g (dry mass) of the mushrooms and were generally higher in cultivated mushrooms than in wild mushrooms. In addition, the ergosterol concentration was higher in the stems than in the caps of the mushrooms examined. Iron, Zn and Cu contents varied between the mushroom species at 8.5–479.9, 13.1–149.7 and 1.62–93.03 mg/kg, respectively, and principal component analysis (PCA) extracted two factors explaining 79.14% of the total variance, suggesting a direct relationship between iron and ergosterol content. This is the first comprehensive study to analyze and evaluate ergosterol concentrations in edible mushrooms from Korea and Serbia.